Rashid Street and its impact in the political twenties of the last century - انوار ناصر حسن (College of Education for Women, 2019)
Rasheed Street has had great importance by the nature of what was seen as being of vital events of a key facility in the Iraqi capital Baghdad since ancient times until now . And such as cultural and historical memory-rich street for Iraq, pulsating nerve since the beginning of the last century thanks to the commercial and intellectual stature, as well as being a tourist landmark frequented alleys most of the tourists coming to Iraq , which counted for them a source of tourist attraction, given the religious diversity of fungal who excelled by the street, as we find in exchange for his Church of the Virgin Mary, the time which was built in the middle of the Caliphs Mosque towering minarets and promised that the oldest and largest of the mosques of the capital Baghdad. Besides that experienced revolutions and a variety of events it made him the station has attracted attention of every vote being folded sweeter and glory Exploits and Iraqi national. Street remained of the places where I met tourism, heritage and memories of the old Baghdad in particular fields, bathrooms and markets, and the old-fashioned urban, which reflects the nature of the architecture Baghdadi since its inception and of building as the boulevards as vivid and profound evidence of the effects and properties involving habits and events linked to cause experienced Baghdad more right different population and its composition.It should be noted in the talk on the street that he like coherent thought in the Iraqi social fabric and who stood firmly against all conspiracies to try to strip it of fragmentation and high national content. Consequently, the Al-Rashid Street is a witness and a teacher of civilization built by the governments deliberated on the rule of the country and missed every one of them reflected the hallmarks of al-Baghdadi, the ancient cultural heritage.